Financial statements, 1961-1968 - Boyle, Edward (London : Her Majesty's Stationery Office, 1967)
The book is a financial statement of United Kingdom between 1961-1962 and 1967-1968 containing the Statement of Revenue presented by the Chancellor of the Exchequer to the house when opening the Budget.
Copy of "Statement of revenue and expenditure as laid before the House by the Chancellor of the Exchequer when opening the budget".
gp 22/01/2019
Ref
Keywords: Financial statements; Great Britain